Detection of prevalence of ?-thalassemia trait in children attending a tertiary pediatric university hospital for non-hematological disorders using red blood cell indices - Mikhael, Neveen Lewis; Zeid, Maha Youssif (Indian Journal of Child Health, 2019)
Background: The red cell indices have been reported to have a major role in detecting ?-thalassemia carriers among children with hypochromic microcytic anemia, but still population studies show controversy on the choice of red cell indices and the cutoff values. Objective: The objective of this study was to detect the percentage of ?-thalassemia carriers among children attending tertiary pediatric university hospital for non-hematological diseases and to test the sensitivity and specificity of different indices and formulas derived from automated hematology analyzer in detecting thalassemia carriers to determine the best index for screening in this age group. Materials and Methods: A cross-sectional study was conducted which included 200 children attending tertiary pediatric university hospital with non-hematological disorders for 6 months. Complete history was recorded for all children and complete blood picture was analyzed on Advia Sysmex analyzer, hemoglobin (hb) electrophoresis on Sebia Capillarys 2 instrument, and iron study in the form of serum iron and total iron-binding capacity. Gene mutation analysis for ?-thalassemia was done by sequence-specific oligonucleotide hybridization for the common mutations for selected cases. Results: We detected a percentage of 7.5% ?-thalassemia trait (TT) and 20% iron deficiency (ID) anemia among studied children. Hb distribution width is the parameter most useful in differentiating ID anemia and TT while Ehsani index was the best calculated index with the highest sensitivity and specificity. Conclusion: There is a lot of interpopulation difference in discriminative power of indices and cell parameters in differentiating ID and TT in children. We advocate larger studies in selected subpopulations to discriminate both diseases.